Analisis strategi pembelajaran berhitung menyenangkan menggunakan media kelereng pada siswa sekolah dasar - Paramitta Purbosari; Mila Puspita Sari; Dinda Widya Hardanti; Anggit Dwi Widiyanto (Nur Science Institute, 2025)
This article examines strategies for basic mathematics learning, particularly counting, designed to be enjoyable through the utilization of marbles as visual and interactive tools. The research aims to analyze enjoyable counting learning strategies using marbles to enhance engagement, motivation, and understanding of basic numeracy concepts among early elementary school children. The method employed is a descriptive, qualitative approach, with in-depth interviews with teachers and students. The results indicate that marbles provide contextual and enjoyable learning experiences that encourage counting activities and align with constructivist and game-based learning theories. This strategy also contributes to the development of affective aspects such as self-confidence and cooperation. In conclusion, this strategy proves effective as an innovative alternative in early mathematics education, with recommendations for broader implementation in school curricula for more inclusive and engaging learning methods.